TINDAK PIDANA PEMILU LEGISLATIF DI KABUPATEN BANYUMAS DAN PURBALINGGA (Studi tentang Kebijakan Formulasi dan Penerapan Undang-Undang No. 10 Tahun 2008 Tentang Pemilihan Umum) - Suharso Agung Basuki (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Legislative General Election 2009 has opening the opportunity to return sovereignty to people. Therefore, in article entitling, Writer interest to study The Crime of legislative general election which formulated in Code Number 10 Year 2008 concerning General Election Of Member of DPR, DPRD, and DPD, and applying of The Crime of General Election in Sub-Province of Banyumas and Purbalingga at GENERAL ELECTION 2009, which conducted by using yuridis normative approach. Pursuant to research, the crime sanction system in general election have the character of cumulative which it is merger of prison sanction and penalty at the same time that imposed to perpetrator. This matter digresses from crime system in KUHP Section 10. 94 of general election crime in Sub-Province of Banyumas and Sub-Province of Purbalingga only 3 processed. Two judge decisions have execution power, whereas the other decision have discharge defendant from all prosecution or ontslag van of ale rechtvervolging (in Sub-Province of Banyumas). Therefore, writer raise recommendation : cause of the number of Parties participant in general election which many collisions in General, so that this code have to reform again, at specially in the case of penalty and prison sanction, and The Stopping of investigation in police level and public attorney don't be easy to conducted.Keyword: general election, crime, sanction, applying of law.